An investigation on supervisor's ability and competency to conduct construction site health and safety induction training in Nigeria. Issue 5 (2nd September 2020) - Okorie, V. N.; Musonda, I.
Abstract: Improving Health and Safety (H&S) performance in the construction industry is dependent on the prevailing culture of an organization. Culture development is also dependent in part on communication between all the parties within an organization. In the construction organization, critical communication occurs between top management and the workers mediated by the supervisors. Consequently, initiatives to develop the right H&S culture may fail if the construction supervisor competencies are overlooked. One of the construction supervisor competencies is the ability to conduct H&S induction training to workers. Induction training communicates the organization's expectations on H&S. This paper reports on a study of supervisor's H&S competency and ability to effectively conduct site H&S induction training to workers. Data was collected through interviews and questionnaires with site supervisors in building and civil engineering construction companies from the South-South Geopolitical zone of Nigeria. Findings revealed inadequate training, lack of management commitment and a limited level of awareness or use of audio/visual communication aids by contracting firms in Nigeria. The use of modern technologies and multilingual skills among supervisors aid effective site H&S induction training and would lead to a positive H&S culture. It is the view of the researchers that supervisor competency is critical to site H&S record and culture improvement.